THE INFLUENCE OF REMUNERATION, MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN TAX OFFICE IN MAKASSAR CITY - Haris Bakaring; Musran Munizu; Wardhani Hakim (Scientia Integritas Utama, 2023)
The purpose of this study was to determine and analyze the effect of reward, motivation and job satisfaction on employee performance in the Makassar City Tax Service Office and the dominant variables affecting employee performance in the Makassar City Tax Service Office. The population taken in this study were all tax employees of the General Directorate of Taxation of Makassar City up to 449 people. The number of samples is 112 people. The sampling technique used in this study was random sampling and the analytical method used was multiple regression analysis. The result is that reward, motivation and job satisfaction influence the performance of tax officials in Makassar with an R Square value of 0.596 or 59.6%, while the remaining 40.4% is influenced by other variables. Reward has a positive and significant partial effect on performance and motivation and job satisfaction has a positive and significant partial effect on the performance of tax officers in KP in Makassar. The most dominant variable affecting the performance of tax officials is motivation with an effect coefficient of 0.543.